A novel visible-light responsive photocatalytic fuel cell with a highly efficient BiVO4/WO3 inverse opal photoanode and a MnO2/graphene oxide nanocomposite modified cathode. (15th March 2019) - Ouyang, Ke; Xie, Shan; Wang, Ping; Zhu, Jian; Zhan, Peng
Abstract: A highly efficient inverse-opal structured BiVO4 /WO3 photoanode and a MnO2 /graphene oxide (GO) nanocomposite modified cathode were successfully synthesized in this paper. The optimized BiVO4 /WO3 inverse opal photoanode achieved a photocurrent density of ∼5.04 mA/cm 2 at 1.2 V vs. Ag/AgCl under simulated AM 1.5 illumination, which was 2.84 and 2.36 times higher than that of WO3 inverse opal photoanode and BiVO4 /WO3 nanoflake photoanode, respectively. The BiVO4 /WO3 inverse opal photoanode was coupled with the MnO2 /GO modified cathode to build up a novel visible-light responsive photocatalytic fuel cell (PFC) system. The as-established PFC showed outstanding power production performances in comparison with the PFC equipped with a bare MnO2 modified cathode. For example, in the former PFC system, the maximum power density and the short circuit current density were ∼66.2 μW/cm 2 and ∼593.5 μA/cm 2, respectively, for comparison, in the latter PFC, the values were ∼30.1 μW/cm 2 and ∼255.9 μA/cm 2, respectively. The degradation experiment for Rhodamine B confirmed successful application of the as-established PFC in pollutant degradation. The mechanism for the significantly enhanced photoelectrocatalytic performances of the PFC was elucidated. The PFC system presented in this paper opened up a new prototype in developing highly efficient devices for energy conversion and environmental protection. Highlights: A highly efficient inverse-opal structured BiVO4 /WO3 photoanode was synthesized. A MnO2 /graphene oxide nanocomposite modified cathode was successfully prepared. The photoanode and the cathode were used to build up a novel PFC system. The PFC showed great performances on power production and pollutant degradation. The mechanism for the enhanced photoelectrocatalytic performances was elucidated.